Do age and sex influence on functional movement in school-age children? (¿Influyen la edad y el sexo en la funcionalidad del movimiento de niños en edad escolar?) - Felipe Garcia-Pinillos; Juan Párraga-Montilla; Luis E Roche-Seruendo; Pedro Delgado-Floody; Cristian P Martínez-Salazar; Pedro A Latorre-Román (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The aim of this study was to determine the influence of age and sex on the functional movement in Spanish primary school children. A group of 172, 6–11 years old children (83 girls and 89 boys), participated in this study. The main outcome measures were the Functional Movement ScreenTM (FMS), sex and chronological age of children. The ANCOVA (BMI as a covariate) revealed significant differences between age groups (p=0.003) but no between-sex differences (p≥0.05) in FMS total score. As for individual FMS tests, significant differences between age groups (p<0.05) were found in the in-line lunge and the shoulder mobility tests; whereas, according to sex, significant differences (p<0.05) were found in the in-line lunge test (under 10 years old group) and the push-up test (under 12 group). The stepwise linear regression analysis revealed BMI as a primary predictor of FMS total score in school age children, but with a significant additional contribution from age (R2= 0.206, p<0.001), whereas the sex was excluded from this model (p=0.097). In conclusion, the results reported in this study suggest that age is a moderate determinant of FMS scores, whereas sex is not a determinant in this battery test in school age children (6-11 years old). This study also highlights that BMI is the primary predictor of FMS total score in school age children, but with a significant additional contribution from age, whereas the sex was excluded from this model.